A Brief Introduction to Web3 : Decentralized Web Fundamentals for App Development. - Jain, Shashank Mohan (Apress L. P., 2023)
Journey into the world of Web3-based application development, its related protocols, and its usage in developing decentralized applications. This book will explain how programmable blockchains are revolutionizing the world of web applications, which can be run on decentralized platforms or peer-to-peer networks like IPFS. You'll start with an introduction to decentralization with a focus on blockchain implementations like Ethereum and Bitcoin. You'll then learn to develop simple decentralized applications (dApps) using Solidity, the language used for developing apps with Ethereum as well as smart contracts, wallets, gateways and NFTs. This book also covers how security and scale are addressed by L2 networks for scaling Bitcoin and Ethereum blockchains. A Brief Introduction to Web3 is your go-to guide for setting up simple Web3 applications using the Ethereum blockchain programming model. What You Will Learn Build NFT tokens Examine Web3 differs from Web2-based applications Understand the fundamentals of blockchain and the corresponding data structures around it See how consensus and trustless computing can be performed using blockchain Use Solidity and Truffle to build Web3 applications Who This Book Is For Software developers and architects who are looking to hone their skills in dApps and web3 applications developed on sound principles of decentralized computing.